STUDENTS’ KNOWLEDGE AND ATTITUDE IN PRACTICING ARTIFICIAL INTELLIGENCE (AI) TOOLS FOR ACADEMIC PURPOSES - Pazil, Nur Syuhada Muhammat; Muhamad, Siti Nor Nadrah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
The increasing integration of Artificial Intelligence (AI) into higher education has transformed how students learn, conduct research, and complete academic tasks. In the era of rapid technological advancement, AI has become an essential element in education, transforming the way students learn, research, and complete academic tasks. However, the extent to which students understand and utilize AI tools effectively remains uncertain. Therefore, this study investigates the factors influencing knowledge and attitude in the use of AI tools for academic purposes among students in the Diploma in Mathematical Sciences program at Universiti Teknologi MARA (UiTM) Arau, Perlis. Data were collected using an online questionnaire comprising four sections covering demographic profiles, knowledge, attitudes, and practices related to AI tool use. A sample of 61 students was selected using convenience sampling, and data analysis was conducted using the Statistical Package for the Social Sciences (SPSS), employing frequency, reliability, correlation, and regression analyses. The Pearson correlation results revealed a moderate positive relationship between students’ knowledge and AI tool use, and a weak positive relationship between attitude and AI tool use. Meanwhile, the regression analysis indicated that knowledge was a significant predictor of AI tool usage. The overall model was significant, suggesting that knowledge plays a more substantial role than attitude in predicting AI use for academic purposes. The study concludes that enhancing students’ knowledge and digital literacy is crucial to encourage the responsible and effective use of AI in education. Institutions should focus on integrating AI literacy, ethical guidelines, and practical training into the curriculum to strengthen students’ academic engagement with AI tools.